Student Perceptions of Collaboration and Scientific Communication Skills in Physics - S. Ratih Uswatun Khasanah; Zulirfan Zulirfan; Syahril Syahril (Jurnal Paedagogy, 2023)
This study analyzes students initial perceptions of their collaboration and scientific communication skills. This method of research was descriptive research with a qualitative and quantitative approach. The subjects of this study were students of class XI MIPA.1 MAN 1 Siak in the 2022/2023 academic year. The data collection technique used in this study was a questionnaire via Google Forms. Data on students collaboration and scientific communication skills perceptions were analyzed using descriptive statistics. The results of data analysis for indicators of collaboration skills are 2.13 in the low category, and scientific communication skills indicators were 1.92 in the low category. From the results of the data analysis, it can be concluded that students initial perceptions of their collaboration and scientific communication skills are in a low category. It is because of students not being used to learning in groups in class due to the online learning process for approximately two years in a row. The lack of training in student collaboration skills results in low scientific communication skills. That is because the essential subjects taught in the emergency curriculum during the pandemic barely touched the real of scientific communication skills.